A randomized control trial to test a peer support group approach for reducing social isolation and depression among female Mexican immigrants - Janet Page-Reeves; Cristina Murray-Krezan; Lidia Regino; Jackie Perez; Molly Bleecker; Daniel Perez; Bill Wagner; Susan Tigert; Elaine L. Bearer; Cathleen E. Willging (BMC, 2021)
Abstract Background Female Mexican Immigrants (FMIs) experience high rates of depression compared with other populations. For this population, depression is often exacerbated by social isolation associated with the experience of immigration. Aim 1. To measure whether a culturally situated peer group intervention will reduce depression and stress associated with the experience of immigration. Aim 2. To test whether an intervention using a "women's funds of knowledge" approach results in improved resilience, knowledge and empowerment. Aim 3. To investigate whether a culturally situated peer group intervention using a women's funds of knowledge approach can give participants a sense and experience of social and physical connection ("emplacement") that is lost in the process of immigration. Methods This mixed-methods study will implement "Tertulias" ("conversational gatherings" in Spanish), a peer support group intervention designed to improve health outcomes for FMI participants in Albuquerque, New Mexico. We will document results of the intervention on our primary hypotheses of a decrease in depression, and increases in resilience and social support, as well as on our secondary hypotheses of decreased stress (including testing of hair cortisol as a biomarker for chronic stress), and an increase in social connectedness and positive assessment of knowledge and empowerment. Discussion This project will address mental health disparities in an underserved population that experiences high rates of social isolation. Successful completion of this project will demonstrate that health challenges that may appear too complex and too hard to address can be using a multi-level, holistic approach. Our use of hair samples to test for the 3-month average levels of systemic cortisol will contribute to the literature on an emerging biomarker for analyzing chronic stress. Trial registration This study was registered with ClinicalTrials.gov on 2/3/20, Identifier # NCT04254198 .